Богдан Берекета – волинський публіцист - Теребус, Оксана Л.; Terebus, O. L. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті зроблено спробу аналізу публіцистичної творчості волинського журналіста Б. Берекети. Розглянуто трудовий шлях, на основі наукових досліджень виведено основні риси творчості публіциста, проаналізовано тематичне різноманіття творів митця, тематичні пласти. Підкреслено актуальність тем, що піднімає публіцист у своїх матеріалах, гуманістичний аспект та вкоріненість у волинську землю. The article deals with the attempt to analyze the publicistic creativity of Volyn journalist B. Berekety. There is no separate monographic study of B. Bereketa’s publicistic creativity, except some single contemporaries mentions in a few lines about him. The aim of this article is to reveal and analyze the B. Bereketa’s publicism. The main features of master’s publicistic creativity are deduced and the thematic diversity of works are analyzed on the basis of the scientific research of publicism. Interesting is the fact, that among the preferences of journalist are the environmental issues, native land, its beauty and uniqueness, the people who inhabit the native land. The particular pages in creativity of the master occupy the articles and essays about the historic figures whose lives and fate are intertwined with the Volyn: D. Bratkovskyj, T. Shevchenko, Lesya Ukrainka, N. Hasevych, I. Stravinskyj, A. Levchanivska, V. Slapchuk and others. The humanistic aspect, the rootedness in the land of Volyn and genre features of B. Bereka’s materials, the relevance of topics, which are raised by the publicist in their materials, are emphasized in this article.
Bohdan Bereketa – Volyn Publicist
Keywords: публіцистика; publicism; формування суспільної думки; forming the public opinion; тема твору; the theme of a work; проблема публіцистичного твору; the problem of publicistic work; жанрові особливості; genre features